2020
DOI: 10.1002/cam4.3029
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin revert insulin‐induced oxaliplatin resistance by activating mitochondrial apoptosis pathway in human colon cancer HCT116 cells

Abstract: Background: Several studies have suggested that drug resistance in colon cancer patients with diabetes may be associated with long-term insulin administration, which in turn decreases the survival rate. Metformin is a commonly used drug to treat diabetes but has been recently demonstrated to have a potential therapeutic effect on colon cancer. This study aimed to elucidate the underlying mechanism by which metformin reverts insulin-induced oxaliplatin resistance in human colon cancer HCT116 cells. Methods: Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…In human cancer cells, metformin inhibited the complex I activity of mitochondrial and cellular respiration, which is regulated by glucose. [ 42 ] Complexes I and III are the main source of ROS production in the mitochondria. Recent studies have emphasized the development of therapeutic strategies that are based on modulation of ROS levels to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In human cancer cells, metformin inhibited the complex I activity of mitochondrial and cellular respiration, which is regulated by glucose. [ 42 ] Complexes I and III are the main source of ROS production in the mitochondria. Recent studies have emphasized the development of therapeutic strategies that are based on modulation of ROS levels to treat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several computational tools and resources have enabled annotating specific P-site as a known drug target (Krug et al, 2019) or correlating the P-site abundance (Abelin et al, 2016; Dele-Oni et al, 2021; Litichevskiy et al, 2018) with drug sensitivity across cell line panels (Frejno et al, 2020). Furthermore, metformin has shown synergistic effects with CRC genotoxic chemotherapy in vitro ( Khader et al ., 2021; Liu et al, 2020; Richard and Martinez Marignac, 2015; Sang et al ., 2020). Therefore, we asked whether we could leverage the metformin phosphoproteomic signatures we discovered to predict the metformin-drug interactions in CRC.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, metformin has shown synergistic effects with CRC genotoxic chemotherapy in vitro (Khader et al, 2021;Liu et al, 2020;Richard and Martinez Marignac, 2015;Sang et al, 2020). Therefore, we asked whether we could leverage the metformin phosphoproteomic signatures we discovered to predict the metformin-drug interactions in CRC.…”
Section: Leveraging the Metformin Signature To Predict Novel Metformi...mentioning
confidence: 99%
“…In addition, as an increased IDacT resulted in poor survival, some approaches could be used to minimize its impact on survival or decrease its incidence based on our aforementioned reasons. For example, metformin (a classical agent for the treatment of diabetes mellitus) could be used to control the fluctuation of glucose and it was also found to be effective in reversing insulin-induced oxaliplatin resistance in human colon cancer HCT-116 cells [ 42 ]; and clinically, metformin was demonstrated to be helpful in improving OS in stage II-III CRC in adjuvant settings [ 43 , 44 ]. In addition, for CRHT, a recent study indicated that administration of pegfilgrastim on the same day as capecitabine-based chemotherapy in gastrointestinal cancers was safe, as it did not require dose reductions or cause a chemotherapy delay [ 45 ].…”
Section: Discussionmentioning
confidence: 99%